2016
DOI: 10.1016/j.vaccine.2016.09.008
|View full text |Cite
|
Sign up to set email alerts
|

A phase 1, open-label, randomized study to compare the immunogenicity and safety of different administration routes and doses of virosomal influenza vaccine in elderly

Abstract: Intradermal delivery significantly improved influenza vaccine immunogenicity compared with intramuscular delivery. Triple dose (45μg) virosomal vaccine did not demonstrate any benefit on vaccine's immunogenicity over 15μg commercial presentation. All treatments were generally safe and well-tolerated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…MPLA (Monophosphoryl Lipid A) is a potent activator of TLR4 that boosts a combined Th1/Th2 response [52]. AddaVax is a squalene-based oil-in-water nano-emulsion adjuvant similar to MF59 that has been licensed in Europe for flu vaccines with the ability to induce a balanced Th1/Th2-type response [53, 54]. Our studies revealed that mice immunized with 25 μg of rAs16 formulated with Alhydrogel produced a similar level of lung larva reduction (38.9%) as observed with 50 μg of rAs16 formulated with ISA720 (36.7%); accompanied by high levels of IgG1 and IL-5, but without IFN-γ or TNF-α production.…”
Section: Discussionmentioning
confidence: 99%
“…MPLA (Monophosphoryl Lipid A) is a potent activator of TLR4 that boosts a combined Th1/Th2 response [52]. AddaVax is a squalene-based oil-in-water nano-emulsion adjuvant similar to MF59 that has been licensed in Europe for flu vaccines with the ability to induce a balanced Th1/Th2-type response [53, 54]. Our studies revealed that mice immunized with 25 μg of rAs16 formulated with Alhydrogel produced a similar level of lung larva reduction (38.9%) as observed with 50 μg of rAs16 formulated with ISA720 (36.7%); accompanied by high levels of IgG1 and IL-5, but without IFN-γ or TNF-α production.…”
Section: Discussionmentioning
confidence: 99%
“…In order to promote a regulatory response to the PIC19-A3 autoantigen we employed the CE-marked MJ600 device to target skin DCs whilst minimising the trauma of intradermal delivery and any ensuing cutaneous inflammation (Mutyambizi et al, 2009). The device has three hollow silicon MNs of 600μm length and has been used extensively in clinical studies to deliver a range of macromolecular formulations including insulin (Kochba et al, 2016), varicella zoster (Beals et al, 2016), polio (Anand et al, 2015;Troy et al, 2015) and seasonal and pandemic influenza vaccines (Della Cioppa et al, 2014;Hung et al, 2012a;Hung et al, 2012b;Levin et al, 2014;Levin et al, 2016;Van Damme et al, 2009). However, whilst there are a number of publications showing successful therapeutic readouts upon use of hollow MNs, there is a paucity of information related to the behaviour of injected materials in the local environment and how formulation or physicochemical drug properties influence distribution and retention in situ (Mansoor et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…The World Health officials are aiming to eliminate measles and such a microneedle patch can be the game changer [12]. Study by Levin et al and Behrens et al confirmed the immunogenicity and safety of intradermal delivery of virosomal influenza vaccine and vaccine containing heat-labile toxin from Escherichia coli against travellers' diarrhea respectively in humans [42,43].…”
Section: Transdermal Routementioning
confidence: 99%